Genetics, genomics, and breeding of black gram [Vigna mungo (L.) Hepper] - Nair, Ramakrishnan M.; Chaudhari, Sunil; Devi, Nagamallika; Shivanna, Aparna; Gowda, Abhishek; Boddepalli, Venkata N.; Pradhan, Hansaraj; Schafleitner, Roland; Jegadeesan, Souframanien; Somta, Prakit (Frontiers in Plant Science, 2024)
Black gram [Vigna mungo (L.) Hepper] is a highly nutritious grain legume crop, mainly grown in South and Southeast Asia, with the largest area in India, and where the crop is challenged by several biotic and abiotic stresses leading to significant yield losses. Improving genetic gains to increase on-farm yields is the primary goal of black gram breeding programs. This could be achieved by developing varieties resistant to major diseases like mungbean yellow mosaic disease, urdbean leaf crinkle virus, Cercospora leaf spot, anthracnose, powdery mildew, and insect pests such as whitefly, cowpea aphids, thrips, stem fly, and bruchids. Along with increasing on-farm yields, incorporating market-preferred traits ensures adoption of improved varieties. Black gram breeding programs rely upon a limited number of parental lines, leading to narrow genetic base of the developed varieties. For accelerating genetic gain, there is an urgent need to include more diverse genetic material for improving traits for better adaptability and stress resistance in breeding populations. The present review summarizes the importance of black gram, the major biotic and abiotic stresses, available genetic and genomic resources, major traits for potential crop improvement; their inheritance, and the breeding approaches being used in black gram for development of new varieties.